2018
DOI: 10.20524/aog.2018.0237
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic submucosal dissection versus endoscopic mucosal resection for type 0-II superficial gastric lesions larger than 20 mm

Abstract: Background:Endoscopic mucosal resection (EMR) and endoscopic submucosal dissection (ESD) are increasingly used for the treatment of superficial gastrointestinal neoplasia. However, the limits and the indications for each technique are still debated. Our retrospective study aimed to compare these techniques in patients with gastric flat lesions larger than 20 mm without the non-lifting sign.Methods:Between January 2013 and July 2016, a total of 36 patients with early gastric flat lesions larger than 20 mm and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Risk factors that indicate a high risk of high-grade dysplasia or malignancy development are a lesion size of >2 cm and the presence of a depression, a rough or reddish surface, and spontaneous bleeding. Although several previous studies have reported that ESD is more effective than EMR for endoscopic resection of superficial gastric neoplastic lesions, 7,[12][13][14] ESD is associated with a high frequency of complications, such as bleeding and perforation. It requires more time and is costlier than EMR.…”
Section: Discussionmentioning
confidence: 95%
“…Risk factors that indicate a high risk of high-grade dysplasia or malignancy development are a lesion size of >2 cm and the presence of a depression, a rough or reddish surface, and spontaneous bleeding. Although several previous studies have reported that ESD is more effective than EMR for endoscopic resection of superficial gastric neoplastic lesions, 7,[12][13][14] ESD is associated with a high frequency of complications, such as bleeding and perforation. It requires more time and is costlier than EMR.…”
Section: Discussionmentioning
confidence: 95%
“…Compared to EMR, ESD allows more precise control of the extent and depth of the resection. Since the resection can be done by directly viewing the dissection plane, and fibrotic lesions can be meticulously managed, ESD is considered more appropriate for securing the resection margin 10 , 11 . This is an important issue, especially in the case of gastric cancer, as a negative resection margin is the core factor of curative resection.…”
Section: Discussionmentioning
confidence: 99%
“…Standard ESD and EFTR techniques were mentioned previously;[ 1 2 ] endoscopic carbon dioxide insufflation was used during the procedure. The defect was closed immediately with endoloop (LeClamp™ Loop-20 and Loop-30; Leo, Changzhou, China) and metallic clips (Micro-Tech, China) using single-channel endoscope (GIF-Q260J; Olympus, Tokyo, Japan).…”
mentioning
confidence: 99%